The Business of Taxes, the Taxation of Business and the Question of Democracy - Anastakis, Dimitry (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2021)
Shirley Tillotson’s Give and Take: The Citizen-Taxpayer and the Rise of Canadian Democracy provides an opportunity to examine this important work’s approach to taxation and business, even if the book’s focus is not primarily focused upon business taxes, businesspeople, or the role of business in taxation policy over the period that that book addresses. This article looks at how Give and Take explores business and taxation, and at how Tillotson engages with some of the key elements and themes in Canadian business history. While not a business historian, Tillotson provides important insights into how we understand the intersection of business and taxation.